Circadian rhythm in mycotoxin-induced immunotoxicity: an emerging regulatory axis? - You, Li; Nepovimova, Eugenie; Sklenarikova, Klara; Wu, Qinghua; Kuca, Kamil (Frontiers in Pharmacology, 2025)
Mycotoxins, toxic secondary metabolites produced by fungi, pose a substantial worldwide health risk due to their widespread contamination of food commodities. Their toxicological effects include organ dysfunction, oxidative stress, and suppression of immune function. Emerging data indicate that circadian rhythm disruption is a critical but underrecognized mechanism contributing to mycotoxin-induced toxicity. This review summarizes current evidence showing that mycotoxins directly interfere with molecular circadian rhythm regulators. Specifically, deoxynivalenol markedly downregulates the expression of BMAL1, CLOCK, and CRY1/2 in hepatic cells. Similarly, zearalenone perturbs the temporal expression of BMAL1, PER2, and NR1D1 in testicular tissue, impairing testosterone biosynthesis. Furthermore, circadian rhythm disruption triggered by mycotoxins may initiate downstream pathological responses, including enhanced ROS generation and immune dysfunction through BMAL1-dependent regulation of PD-L1 expression. Importantly, a reciprocal feedback loop appears to exist wherein oxidative stress intensifies circadian rhythm disruption, which in turn promotes ROS accumulation and further immune impairment. These insights establish circadian rhythm disruption as a central mediator of mycotoxin-related toxicity and highlight BMAL1 as a potential therapeutic target. Nonetheless, experimental validation remains limited, and further mechanistic studies are required. We propose that circadian rhythm disruption may serve as an integrative node within the mycotoxin toxicity pathway, linking oxidative imbalance to immunosuppressive outcomes.